A spectral mapping theorem for semigroups solving PDEs with nonautonomous past. (7th September 2003) - Fragnelli, Genni
Abstract : We prove a spectral mapping theorem for semigroups solving partial differential equations with nonautonomous past. This theorem is then used to give spectral conditions for the stability of the solutions of the equations.